129PMonitoring patient-specific mutation in ctDNA and CTC for tumour response evaluation after neoadjuvant chemotherapy in advanced gastric adenocarcinoma (NCT03425058). (24th November 2019) - Fu, T
Abstract: Background: To verify the value of ctDNA and CTC as biomarkers for tumor response in the neoadjuvant chemotherapy (nCRT) treatment of locally advance gastric adenocarcinoma. Methods: A total of 50 patients were enrolled. 20ml of plasma were collected at 3 points: before nCRT; after 2 cycles of nCRT; and after surgery. Firefly ctDNA NGS assays were used to track ctDNA mutations previously. Using patient-specific mutation derived from exome sequencing of tumor tissues samples. Tumor response data by CT were also collected. CTCs in 7ml peripheral blood were separated by a negative enrichment method and identified by FISH using two frequently proliferation chromosome probes, CEP8 and CEP17. Meanwhile, the HER2 expression in CTCs was determined by FISH and immunofluorescence. CEP8+ and/or CEP17+, DAPI+, CD45- cell were justified as CTCs, HER2 FISH+ or HER2 IF+, DAPI+, CD45- cells were justified as HER2 positive CTCs. Results: A total of 10-20 somatic SNV or indel mutation were successfully identified for each patient. In comparison to basal line value of pre-chemotherapy blood, the ctDNA loading were decreased in post-chemotherapy specimens of 8 patients with TRG1 by histopathological grading or partial and complete response by CT scan. However, the amount of ctDNA in 25 patients diagnosed as TRG 2 or 3 showed minor changes during the neoadjuvant therapy. After surgery, 32 patients showed undetectable ctDNA in blood while 3 patients showed residual trace ctDNA. 22 patients have integral FISH data (CTCs before, after nCRT and after surgery range from 0-29, average: 4.9, 2.7 and 4.0, positive rate: 82%, 73% and 73%), and 12 have integral HER2 data. The dynamic variations were coincidence to the clinical evaluation. For HER2, we found three positive model in CTCs, single FISH or IF positive or double positive. Double positive HER2-CTCs are found in some patients. By negative enrichment and FISH, CTCs can be detected at a low cutoff of 2 cells in 73%∼82% patients. Conclusions: The ctDNA and CTC alteration during neoadjuvant therapy is consistent with conventional histopathological grading and radiological response assessment. Clinical trial identification: NCT03425058. Legal entity responsible for the study: The author. Funding: Has not received any funding. Disclosure: The author has declared no conflicts of interest.